2019
DOI: 10.1016/j.jot.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of intravenous tranexamic acid in hip fracture surgery: A systematic review and meta-analysis

Abstract: ObjectiveThe present meta-analysis was conducted to compare the efficacy and safety of intravenous application of tranexamic acid (TXA) with placebo in patients with hip fracture undergoing hip surgeries.MethodsPubMed, EMBASE and Cochrane Library were searched from inception until March 2018. A combined searching strategy of subject words and random words was adopted. Only randomized clinical trials were included. The comparisons regarding transfusion rate, total blood loss, intraoperative blood loss, postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 47 publications
6
51
0
Order By: Relevance
“…There is compelling evidence suggesting that the intraoperative administration of TXA reduces transfusion rates and bleeding complications in arthroplasty patients 44 , 45 . The benefit of TXA appears to also apply to hip fracture patients 41 , 42 , 46 , 47 ; however, additional research is required to fully elucidate this with respect to preoperative anemia and is outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence suggesting that the intraoperative administration of TXA reduces transfusion rates and bleeding complications in arthroplasty patients 44 , 45 . The benefit of TXA appears to also apply to hip fracture patients 41 , 42 , 46 , 47 ; however, additional research is required to fully elucidate this with respect to preoperative anemia and is outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with previous reports. In previous reports, intravenous TXA can increase the postoperative Hb level of patients with TKA, reduces the trend of postoperative blood loss, and does not cause thrombus [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, nowadays more and more geriatric patients are suffering from hip fractures, for some of them it may be better to receive THA [39]. Qi et al [40] demonstrated that intravenous TXA reduced total blood loss and transfusion requirements, but did not increase the incidence of thromboembolic events in patients who suffered from hip fractures and underwent THA . Although Tranexamic acid was discovered more than 50 years ago, the clinical utilization of tranexamic to reduce blood loss and transfusion requirements became popular in the past decade.…”
Section: Discussionmentioning
confidence: 99%